The great serum race : blazing the Iditarod Trail - Miller, Debbie S. (Walker & Co., 2002)
The story of the heroic role played by sled dogs, including the Siberian husky Togo, in the delivery of antitoxin serum to those stricken with diphtheria in 1925 Nome. Includes historical notes about the event as well as about the Iditarod Sled Dog Race which commemorates it.